2018
DOI: 10.1161/strokeaha.117.020315
|View full text |Cite
|
Sign up to set email alerts
|

First Pass Effect

Abstract: The achievement of complete revascularization from a single Solitaire thrombectomy device pass (FPE) is associated with significantly higher rates of good clinical outcome. The FPE is more frequently associated with the use of balloon guide catheters and less likely to be achieved with internal carotid artery terminus occlusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
231
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 525 publications
(305 citation statements)
references
References 29 publications
12
231
2
Order By: Relevance
“…Interestingly, our study showed that the most common clinical factors that are used to determine eligibility for endovascular therapy, such as NIHSS severity, location of ELVO, symptom onset to treatment or patient age were not predictive of the ability to achieve FPE. Likewise, in NASA most clinical and demographic factors such as stroke severity or the use of IV tPA did not influence the success of FPE with an exception of the presence of ICA occlusion, which was a negative independent predictor of FPE (2).…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Interestingly, our study showed that the most common clinical factors that are used to determine eligibility for endovascular therapy, such as NIHSS severity, location of ELVO, symptom onset to treatment or patient age were not predictive of the ability to achieve FPE. Likewise, in NASA most clinical and demographic factors such as stroke severity or the use of IV tPA did not influence the success of FPE with an exception of the presence of ICA occlusion, which was a negative independent predictor of FPE (2).…”
Section: Discussionmentioning
confidence: 79%
“…Recently, the firstpass effect (FPE) defined as complete recanalization achieved with a single thrombectomy device pass was described as a novel metric of ET success (2). First described in the analysis of the North American Solitaire Acute Stroke (NASA) Registry database, FPE served as an independent predictor of good clinical outcome after stent retriever thrombectomy (modified Rankin Scale score 0-2 in 61% in FPE vs. 35% in non-FPE cohort; P = 0.013) (2,3). The benefit of FPE on clinical outcome was subsequently confirmed by the Analysis of Revascularization in Ischemic Stroke With EmboTrap (ARISE II) study of the EmboTrap thrombectomy device (4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourth, the technical efficacy outcome of substantial reperfusion within 3 passes, although it is the leading technical endpoint used in recent trials, is beginning to reach a ceiling effect with achievement rates approaching 85–90% in recent trials. More stringent reperfusion endpoints, such as first pass excellent reperfusion (FP-TICI 2c-3) or time to achievement of substantial TICI 2b-3 reperfusion are associated with further incremental gains in final clinical outcome and may play more important roles as technical efficacy outcomes in clinical trials in the future ( 31 ). The MCID for FP-TICI 2c-3 and other, more advanced, final reperfusion status outcomes are likely to be similar but not exactly equal to that for substantial reperfusion within 3 passes.…”
Section: Discussionmentioning
confidence: 99%
“…Studies also suggest that multiple device passes are associated with a lower rate of both successful revascularization and favorable clinical outcome7 and higher rates of hemorrhagic transformations 8. A new index has thus been proposed: the ‘first pass effect’ (FPE), which symbolizes ‘the ideal scenario’ and is defined by a (near-)complete revascularization after a single pass of the device with no rescue therapy 9 10. Zaidat et al have shown that patients with a FPE had a significantly improved outcome.…”
Section: Introductionmentioning
confidence: 99%